Preliminary experiments on the cultivation of Chlorella sorokiniana in different types of agro-industrial wastewater: insights from sequencing batch reactor experiments - Argyri Xenaki; Effrosyni-Taxiarchoula Karagianni; Eirini Zkeri; Georgia Gatidou; Athanasios S. Stasinakis (Journal of Applied Phycology, 2026)
The use of microalgae in wastewater treatment offers a sustainable approach to environmental management and resource recovery. This study investigated the potential of Chlorella sorokiniana cultivated in different types of agro-industrial wastewater, including effluents from dairy processing, citrus fresh juice production, and chili sauce manufacturing, for simultaneous pollutants removal and high-value biomass generation. The microalgae were cultivated under continuous and periodic illumination (51.51 and 17.62 μmol photons m −2 s −1 , respectively) in 2-L or 5-L sequencing batch reactors, with and without nitrogen supplementation, using both one-stage and two-stage bioreactor systems. Biomass growth rates were comparable under both continuous (0.13 ± 0.9 mg day −1 ) and periodic illumination (0.12 ± 0.12 mg day −1 ), with no statistically significant differences observed among the various types of wastewater. The removal of COD and NH 4 -N in one-stage experiments ranged up to 90 ± 3% and 89 ± 3%, respectively, while COD removal was higher in experiments conducted under periodical illumination and with no nitrogen addition. No significant differences in the protein content of biomass were observed among the tested wastewater types, while nitrogen supplementation enhanced protein biosynthesis. In one-stage experiments, the highest lutein and chlorophyll- a concentrations were observed in the bioreactor with chili sauce wastewater, reaching 12.21 mg g −1 and 62.5 mg g −1 , respectively, while periodic illumination improved the ability of microalgae to synthesize β-carotene and chlorophyll-a. In two stage experiments, the higher concentrations of lutein were observed after the end of the 1st stage. Based on the results, C. sorokiniana can successfully grow in various types of agro-industrial wastewater, efficiently remove pollutants, and yield biomass enriched with valuable nutrients, including pigments and proteins.

Evaluation of a pilot system coupling thermal and ultrasound pretreatment, anaerobic digestion and hydrothermal carbonization for sewage sludge treatment and per- and polyfluoroalkyl substances removal - Evdokia Gkalipidou; Asimina Koukoura; Ioanna Savvanidou; Marios G. Kostakis; Dimitrios Triantafyllos Gerokonstantis; Petros Mastoras; Georgia Gatidou; Michail S. Fountoulakis; Stergios Vakalis; Olga S. Arvaniti; Nikolaos S. Thomaidis; Olga-Ioanna Kalantzi; et al. (Chemical Engineering Journal, 2026)

Fungal-assisted harvesting of Chlorella sorokiniana cultivated in diluted anaerobic digestate using the edible mushroom Pleurotus ostreatus - Spyridoula Schiza; Eirini Sventzouri; Konstantinos Pispas; Ioanna Petousi; Demetrios-Francis Lekkas; Athanasios S. Stasinakis; Michael Kornaros; Michail S. Fountoulakis (Environmental Science and Pollution Research, 2025)

Occurrence of per- and polyfluoroalkyl substances, pesticides, pharmaceuticals, and heavy metals in Greek backyard chicken eggs and estimation of the consumption risk - Olga S. Arvaniti; Dimitrios Triantafyllos Gerokonstantis; Christoforos Bouzoukas; Maria Aloupi; Georgios Gkotsis; Antigoni Konomi; Artemis Mastrotheodoraki; Athanasia Iliopoulou; Marios Kostakis; Marilena Dasenaki; Nikolaos S. Thomaidis; Athanasios S. Stasinakis (Science of The Total Environment, 2025)

Impact of granular activated carbon, voltage application and sewage sludge pretreatment on mesophilic anaerobic digestion performance and per- and polyfluoroalkyl substances removal - Evdokia Gkalipidou; Michalis Deligiannis; Georgia Gatidou; Emma R. Knight; Ian J. Allan; Marios G. Kostakis; Dimitrios Triantafyllos Gerokonstantis; Olga S. Arvaniti; Nikolaos S. Thomaidis; Ioannis Vyrides; Michail S. Fountoulakis; Athanasios S. Stasinakis (Journal of Environmental Chemical Engineering, 2025)

Study on the removal of major pollutants, benzotriazoles, and hydroxybenzothiazole in conventional and microbial electrochemistry – enhanced constructed wetlands - Asimina Koukoura; Athanasios Bollas; Eva Psalti; Georgia Gatidou; Simos Malamis; Michail S. Fountoulakis; Athanasios S. Stasinakis (Journal of Water Process Engineering, 2025)

Using a mixture of perlite and sponge bio-carriers as substrate material in vertical flow-constructed wetlands for cheese production wastewater treatment - Dimitra Kotsia; Xavier Goux; Jimmy Roussel; Athanasios S. Stasinakis; Michail S. Fountoulakis (Journal of Environmental Management, 2025)

Circular water management in agriculture: Screening of contaminants of emerging concern in a real-world water-soil-crop system and human health risk assessment - Elena Koumaki; Antigoni Konomi; Georgios Gkotsis; Maria-Christina Nika; Taxiarchis Seintos; Evangelos Statiris; Niki Maragou; Nikolaos S. Thomaidis; Nikolaos Kouris; Daniel Mamais; Athanasios S. Stasinakis; Simos Malamis; et al. (Journal of Hazardous Materials, 2025)

Comparing the performance of microbial electrochemical assisted and aerated treatment wetlands in pilot-scale: Removal of major pollutants and organic micropollutants - Asimina Koukoura; Taxiarchis Seintos; Evangelos Statiris; Evridiki Barka; Georgia Gatidou; Constantinos Noutsopoulos; Simos Malamis; Daniel Mamais; Fabio Masi; Anacleto Rizzo; Michail S. Fountoulakis; Athanasios S. Stasinakis (Science of The Total Environment, 2024)

A new approach on the management of landfill leachate reverse osmosis concentrate: Solar distillation coupled with struvite recovery and biological treatment - Konstantinos Tsompanoglou; Athanasia Iliopoulou; Petros Mastoras; Athanasios S. Stasinakis (Chemosphere, 2024)

Study on the fate of per- and polyfluoroalkyl substances during thermophilic anaerobic digestion of sewage sludge and the role of granular activated carbon addition - Michalis Deligiannis; Evdokia Gkalipidou; Georgia Gatidou; Marios G. Kostakis; Dimitrios Triantafyllos Gerokonstantis; Olga S. Arvaniti; Nikolaos S. Thomaidis; Ioannis Vyrides; Sarah E. Hale; Hans Peter Arp; Michail S. Fountoulakis; Athanasios S. Stasinakis (Bioresource Technology, 2024)

Winery wastewater treatment by microalgae Chlorella sorokiniana and characterization of the produced biomass for value-added products - Eirini Zkeri; Maria Mastori; Argyri Xenaki; Evangelia Kritikou; Marios Kostakis; Marilena Dasenaki; Niki Maragou; Michail S. Fountoulakis; Nikolaos S. Thomaidis; Athanasios S. Stasinakis (Environmental Science and Pollution Research, 2024)

Treatment of real laundry wastewater using vertical flow constructed wetland planted with the ornamental climbing plant Trachelospermum jasminoides: assessing the removal of conventional pollutants and benzotriazoles - Aimilia Stefanatou; Lydia Vouzi; Ioanna Petousi; Asimina Koukoura; Georgia Gatidou; Athanasios S. Stasinakis; Michail S. Fountoulakis (Environmental Science and Pollution Research, 2024)

Cultivation of the macrophyte Lemna minor and the microalgae Chlorella sorokiniana in thermal mineral waters: Biomass characteristics, radioisotopes and heavy metals content - Alexandra Katsara; Eirini Zkeri; Maria Aloupi; Filothei K. Pappa; Christos Matsoukas; Athanasios S. Stasinakis (Environmental Pollution, 2024)

Use of ornamental plants in floating treatment wetlands for greywater treatment in urban areas - Aimilia Stefanatou; Evrydiki Markoulatou; Ilias Koukmenidis; Lydia Vouzi; Ioanna Petousi; Athanasios S. Stasinakis; Anacleto Rizzo; Fabio Masi; Triantaphyllos Akriotis; Michail S. Fountoulakis (Science of The Total Environment, 2024)

Vertical flow constructed wetlands as green facades and gardens for on-site greywater treatment in buildings: Two-year mesocosm study on removal performance - Aimilia Stefanatou; Michail Lagkadas; Ioanna Petousi; Spyridoula Schiza; Athanasios S. Stasinakis; Nikolaos Fyllas; Michail S. Fountoulakis (Science of The Total Environment, 2024)

Application of a pilot-scale solar still for wine lees management: characterization of by-products and valorization potential - Petros Mastoras; Eirini Zkeri; Anthi Panara; Marilena E. Dasenaki; Niki C. Maragou; Stergios Vakalis; Michail S. Fountoulakis; Nikolaos S. Thomaidis; Athanasios S. Stasinakis (Journal of Environmental Chemical Engineering, 2023)

Leachate management in medium- and small-sized sanitary landfills: a Greek case study - Olga P. Koutsou; Christoforos Mandylas; Michail S. Fountoulakis; Athanasios S. Stasinakis (Environmental Science and Pollution Research, 2023)
The sustainable management of landfill leachates remains a matter of important concern in many countries. We used as case study a medium-sized Greek landfill, and we initially investigated the performance of the existing secondary leachate treatment system. The activated sludge process removed chemical oxygen demand (COD), biochemical oxygen demand (BOD), NH 4 -N, and PO 4 -P by 55%, 84%, 94%, and 14%, respectively, but the effluents did not meet the legislation requirements for discharge or reuse. Afterwards, different management options of these effluents (co-treatment with sewage in the centralized treatment plant, onsite tertiary treatment with reverse osmosis, granular activated carbon (GAC), ozonation, photo-Fenton, or constructed wetlands) were evaluated regarding their operational costs and environmental footprint. The use of constructed wetlands presented the lower operational cost, energy requirements, and greenhouse gas (GHG) emissions, not exceeding 21.5 kg CO 2eq /day. On the other hand, the power consumption and the GHG emissions of the other on-site technologies ranged from 0.37 kWh/m 3 and 5.56 kg CO 2eq /day (use of GAC) to 39.19 kWh/m 3 and 588.6 kg CO 2eq /day (use of ozonation), respectively. The co-treatment of the leachates with municipal wastewater required 0.6 kWh/m 3 and emitted 30.18 kg CO 2eq /day. For achieving zero-discharge of the treated leachates, a system consisting of constructed wetlands and evaporation ponds in series was designed.

Combined use of strictly anaerobic MBBR and aerobic MBR for municipal wastewater treatment and removal of pharmaceuticals - Athanasia Iliopoulou; Olga S. Arvaniti; Michalis Deligiannis; Georgia Gatidou; Ioannis Vyrides; Michalis S. Fountoulakis; Athanasios S. Stasinakis (Journal of Environmental Management, 2023)

Use of climbing and ornamental plants in vertical flow constructed wetlands treating greywater - Aimilia Stefanatou; Spyridoula Schiza; Ioanna Petousi; Anacleto Rizzo; Fabio Masi; Athanasios S. Stasinakis; Nikolaos Fyllas; Michail S. Fountoulakis (Journal of Water Process Engineering, 2023)

Granular activated carbon stimulates biogas production in pilot-scale anaerobic digester treating agro-industrial wastewater - Demetrios Kalantzis; Ioannis Daskaloudis; Tim Lacoere; Athanasios S. Stasinakis; Demetris F. Lekkas; Jo De Vrieze; Michail S. Fountoulakis (Bioresource Technology, 2023)

Consumption-based approach for predicting environmental risk in Greece due to the presence of antimicrobials in domestic wastewater - Evangelia I. Iatrou; Athanasios S. Stasinakis; Nikolaos S. Thomaidis (Environmental Science and Pollution Research, 2014)

Occurrence of endocrine disrupters and selected pharmaceuticals in Aisonas River (Greece) and environmental risk assessment using hazard indexes - Athanasios S. Stasinakis; Smaragdi Mermigka; Vasilios G. Samaras; Eleni Farmaki; Nikolaos S. Thomaidis (Environmental Science and Pollution Research, 2012)

Fate and Biotransformation of Metal and Metalloid Species in Biological Wastewater Treatment Processes - Athanasios S. Stasinakis; Nikolaos S. Thomaidis (Critical Reviews in Environmental Science and Technology, 2010)

Occurrence of Organotin Compounds in the Aquatic Environment of Greece - Nikolaos S. Thomaidis; Athanasios S. Stasinakis; Georgia Gatidou; Roberto Morabito; Paolo Massanisso; Themistokles D. Lekkas (Water, Air, & Soil Pollution, 2007)

Effect of arsenic and mercury speciation on inhibition of respiration rate in activated sludge systems - Athanasios S. Stasinakis; Nikolaos S. Thomaidis; Apostolos S. Giannes; Themistokles D. Lekkas (Environmental Science and Pollution Research, 2003)